High SVR12 With 8-Week Course of Direct-Acting Antivirals in Adolescents and Children With Chronic Hepatitis C: A Comprehensive Analysis - Fu, Zuqiang; Dong, Chen; Ge, Zhijun; Wang, Chunhui; Zhang, Yun; Shen, Chao; Li, Jun; Zhu, Chuanlong; Wang, Yan; Huang, Peng; Yue, Ming (Frontiers in Medicine, 2021)
Direct-acting antiviral (DAA) treatment for 8 weeks has a sustained virological response rate in adults with chronic hepatitis C. We have conducted a systematic review and meta-analysis to compare the efficacy and safety of the 8-week vs. 12/24-week DAA treatment in adolescents and children with CHC. The PubMed, Web of Science, and Cochrane databases were searched for the relevant articles from January 1, 2017 to August 28, 2020 and further screened for literature reviews on April 1, 2021. Pool proportions with 95% CIs for SVR12 were summarized with fixed/random effects models using Freeman–Tukey double arcsine transformation. Subgroup analysis was used to explore the source of heterogeneity. Thirty-six relevant publications were identified. For adolescents aged 12–17 years old, the pooled SVR12 and AE rate were 99.4% (95% CI: 98.7–99.9) and 34.7% (95% CI: 31.9–37.6). No one discontinued treatment due to drug intolerance. In addition, the SVR12 adolescents treated for 12 and 8/24 weeks were 99.3% (95% CI: 98.4–99.9) and 100%, respectively. The pooled SVR12 rate, AEs, and SAEs for children younger than 12 years were 98.9% (95% CI: 97.3–99.8), 51.6% (95% CI: 47.0–56.2), and 1.1% (95% CI: 0.4–2.5), respectively. The most common AE was fatigue (28.4%). The SVR12 was 98.8% (95% CI: 97.1–99.8) and 100% for the pediatric patients treated for 12 weeks and 8/24 weeks, respectively. Taken together, DAAs are generally effective against CHC and well-tolerated by the adolescents and children. A treatment duration of 8 weeks is equally effective and safe as 12/24 weeks in this demographic group.